The Correlation of Women’s knowledge of Shildbearing Age (15-49 Years) about Breast Cancer and Motivation to do Breast Self-Examination (BSE) - Wiwik Muhidayati; Nur Azizah; Lusi Afriyani; Kartika Ria Ningrum (STIKes Patria Husada Blitar, 2021)
Regular breast self-examination is a way to detect early signs of problems in the breasts. The purpose of the study was to determine the correlation of womensâ€™ knowledge of childbearing age (15-49 years) about breast cancer and the motivation to carry out breast self-examination (BSE) in Jetak Village, Bojonegoro District, Bojonegoro Regency in 2020. The method was correlational analytic with cross sectional approach with a total sample of 85 respondents taken by simple random sampling technique. The data collection instrument used a questionnaire. After the data was collected, the data was processed and analyzed using the Spearman Rho statistical test. The results of this study indicated that the majority of respondents had good knowledge as much as 26 (81.3%) and had a strong motivation to perform breast self-examination (BSE). And after being tested statistically using the Spearman Rho statistical test with a value of ï² : 0.05, the value of ï² : 0.000 < (0.05), which meant there was a correlation between Womenâ€™s knowledge of childbearing age (15-49 years) about breast cancer and motivation do BSE. The conclusion was there was a correlation between Womenâ€™s knowledge of childbearing age (15-49 years) about breast cancer and motivation to perform breast self-examination (BSE).Â